Coding technology of passive internet of things - Yibing YANG; Rongtao XU; Xia CHEN; Gongpu WANG; Bo AI (物联网学报)
Passive backscatter communication can free wireless sensors from limited-life batteries and heavy manual maintenance, and will also reduce their hardware cost.Passive backscatter communication is one of the key technologies to realize the passive internet of things (IoT).Due to the limited resources of passive sensor nodes, how to use coding technology to improve system reliability has become a challenging problem for passive IoT.The coding and decoding technologies of passive nodes in the passive IoT were focused on.Firstly, the development history of traditional channel coding and the existing RFID channel coding and decoding schemes were systematically expounded.Then, three suitable coding schemes were selected for passive backscatter communication technology.Finally, the performance of these three encoding schemes were compared by simulation and the advantages and disadvantages were summarized.